Concerning Increase In Tax Cigarette (Tufts Archival Research Center, 2007)
Handwritten; Handwritten letter by an unknown author from Cocoa, FL, to an unknown recipient discussing proposed cigarette tax increases. Explains author's position as someone on a fixed income that has been smoking for 70 years without ever getting sick, and has written to Senators and Congressman about preventing the tax increase. Asks recipient what else can be done to prevent the increase as it will put him/her in a precarious economic position.